(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2022)
A total of 82 adult cow, 24 adult calves , which their ages more than one year , and 38 female calves, 29 male calves which their ages less than one year , are examined during the period from August /2021 till Feb/2022 to detect their infection with Giardia parasite .Its found that 18 of the adult animals infected with cyst (16.98%) while 3 only infected with trophozoites (4.47%) . The animals that their ages less than one year exhibited less rate of infection (8.49% and 7.46% with cyst and trophozoite respectively). According to months of the year , August show the highest rate of infection especially among adult male animals and small female animals (40% and 50% respectively ) . The study recorded Giardia parasite in cattle’s for the first time in Al-Kufa city , Al-Najaf Al-Ashraf .